Morphological substantiation of ultrasonographic criteria of an acute cholecystitis and its paravesical complications - T. I. Tamm; I. G. Zulfugarov; V. V. Nepomnyashchiy; O. P. Zackarchuck; I. M. Mamontov; K. O. Kramarenko; O. M. Rechetnyack (Клінічна хірургія)
Objective. To improve quality of diagnosis of paravesical complications in patients, suffering an acute cholecystitis, using demonstration of interrelationship of changes in the gallbladder wall histostructure and its echogram data.